Catalyst composition, catalytic activity promotion method, catalyst composition production method, and ammonia synthesis method using catalyst composition

CN118201707BActive Publication Date: 2026-10-09THE JAPAN SCI & TECH AGENCY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202280073997.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-09
Filing Date
2022-11-02
Publication Date
2026-10-09
Estimated Expiration
2042-11-02

AI Technical Summary

Benefits of technology

[0121]The catalyst composition of the present invention can improve catalyst performance by adding catalyst additives. Furthermore, the catalyst composition of one embodiment of the present invention exhibits high ammonia synthesis activity when used as a hydrogenation catalyst, particularly as a catalyst for ammonia synthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004824017200000391
    Figure BDA0004824017200000391
  • Figure HDA0004824017210000011
    Figure HDA0004824017210000011
  • Figure HDA0004824017210000012
    Figure HDA0004824017210000012
Patent Text Reader

Abstract

This invention provides a catalyst composition whose performance can be improved by adding a catalyst additive. The catalyst composition is characterized by comprising formula (1): L m A n The catalyst additives represented are those containing formula (2): M p O q C w N s H t The catalyst is a chemical reaction catalyst. (In formula (1), L represents at least one element selected from the group consisting of transition elements and Al, A represents at least one element selected from the group consisting of Si, O, N and C, m represents a value greater than 1, and n represents a value greater than 0. In formula (2), M represents one or more elements selected from the group consisting of typical elements and transition elements, wherein M does not simultaneously include Al and Ca, p represents a value greater than 0, q represents a value greater than 0, w represents a value greater than 0, s represents a value greater than 0, and t represents a value greater than 0. Among them, q, w, s, and t are not simultaneously 0.)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to catalyst compositions, methods for promoting catalytic activity, methods for manufacturing catalyst compositions, and methods for ammonia synthesis using catalyst compositions.

[0002] This application claims priority based on Japanese Patent Application No. 2021-182700, filed in Japan on November 9, 2021, the contents of which are incorporated herein by reference. Background Technology

[0003] Catalysts are often used to accelerate chemical reactions. An example of such a chemical reaction is the ammonia synthesis reaction, specifically hydrogenation. A representative ammonia synthesis method is the Haber-Bosch process. The Haber process uses a double-promoted iron catalyst (Fe3O4 containing a few percent by mass of Al2O3 and K2O) to directly react a mixture of nitrogen and hydrogen with the catalyst under high temperature and high pressure conditions to produce ammonia. Currently, the industrially used technology remains almost entirely the same manufacturing process as when it was first developed.

[0004] On the other hand, methods for synthesizing ammonia at temperatures lower than the Haber process were investigated. Catalysts capable of synthesizing ammonia through contact with nitrogen and hydrogen were studied, with transition metals as their catalytically active components. Among these, a method was proposed as an efficient one, in which ruthenium (Ru), as the catalytically active component, is supported on various supports and used as a catalyst for ammonia synthesis (e.g., Patent Document 1).

[0005] There exist compounds that are calcium aluminosilicates composed of CaO, Al2O3, and SiO2, and have a crystal structure similar to that of calcium aluminosilicate, and are called "calcium aluminosilicate-type compounds". The representative composition of the aforementioned calcium aluminosilicate-type compounds is represented by 12CaO·7Al2O3. In addition, they have a structure in which two oxygen atoms, as "free oxygen", are encapsulated in the space within the cage formed by their crystal framework.

[0006] The inventors of this application have discovered that a catalyst obtained by supporting a transition metal as a catalytically active component on a calcium aluminate compound (hereinafter referred to as C12A7 electron compound) formed by replacing the free oxygen in the aforementioned calcium aluminate compound with electrons has high activity as a catalyst for ammonia synthesis. (Patent Document 2).

[0007] Furthermore, the inventors of this application have discovered that supported metal catalysts using metal amino compounds, metal hydrides, typical element oxides, metal hydrides, alkaline earth metal oxides, etc., exhibit high activity as catalysts for ammonia synthesis (Patent Documents 3-6). Additionally, supported metal catalysts using composite oxides have been disclosed as catalysts for ammonia synthesis (Patent Document 7).

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 2006-231229

[0011] Patent Document 2: International Publication No. 2012 / 077658

[0012] Patent Document 3: International Publication No. 2016 / 088896

[0013] Patent Document 4: International Publication No. 2017 / 082265

[0014] Patent Document 5: Japanese Patent Application Publication No. 2019-126776

[0015] Patent Document 6: International Publication No. 2021 / 172107

[0016] Patent Document 7: International Publication No. 2019 / 59190 Summary of the Invention

[0017] The problem that the invention aims to solve

[0018] Ammonia synthesis based on the Haber process, which mainly uses dual-promoting iron catalysts, has been put into practical use. However, due to the need for high temperature and high pressure conditions, it faces problems such as heavy burdens in terms of equipment and cost.

[0019] The supported metal catalysts described in Patent Document 1 typically use carbonaceous supports such as activated carbon or inorganic oxide supports. However, it cannot be said that these supported metal catalysts always possess sufficient performance in practical use. Furthermore, regarding the supported metal catalysts described in Patent Documents 2-6, their catalytic activity may not be fully satisfied depending on the circumstances and conditions.

[0020] That is, there is a need for ammonia synthesis catalysts with superior catalytic activity that can maintain sufficient reactivity even under conditions such as lower temperature and lower pressure compared to the Haber process reaction conditions.

[0021] Methods for solving problems

[0022] The inventors of this application discovered the catalyst composition of the present invention, which can improve the performance of a catalyst by adding catalyst additives, thereby completing the present invention.

[0023] That is, the essence of this invention is:

[0024] [1] A catalyst composition, characterized in that it comprises:

[0025] The catalyst additives represented by the following formula (1), and

[0026] A chemical reaction catalyst containing a catalytic substance represented by the following formula (2).

[0027] L m A n (1)

[0028] (In formula (1),)

[0029] L indicates that at least one element is selected from the group consisting of free transition elements and aluminum (Al).

[0030] A represents at least one element selected from the group consisting of silicon (Si), oxygen (O), nitrogen (N), and carbon (C).

[0031] (m represents a value greater than 1, and n represents a value greater than 0.)

[0032] M p O q C w N s H t (2)

[0033] (In formula (2),)

[0034] M indicates that one or more elements are selected from a group consisting of typical elements and transition elements. M may not simultaneously include aluminum (Al) and calcium (Ca).

[0035] p represents a value greater than 1, q represents a value greater than 0, w represents a value greater than 0, s represents a value greater than 0, and t represents a value greater than 0. Note that q, w, s, and t cannot all be 0 simultaneously.

[0036] [2] The catalyst composition as described in [1], wherein the aforementioned chemical reaction catalyst and the aforementioned catalyst composition have hydrogenation reaction activity,

[0037] The hydrogenation reaction activity of the aforementioned catalyst composition is higher than that of the aforementioned chemical reaction catalyst.

[0038] [3] The catalyst composition as described in [2], wherein the hydrogenation reaction activity of the aforementioned chemical reaction catalyst and the aforementioned catalyst composition is ammonia synthesis activity.

[0039] [4] The catalyst composition as described in [2] or [3], wherein the aforementioned catalyst additive does not have hydrogenation reaction activity.

[0040] [5] The catalyst composition as described in any one of [1] to [4], wherein, in the aforementioned formula (1), L is selected from at least one of the group consisting of titanium (Ti), iron (Fe), nickel (Ni) and aluminum (Al).

[0041] [6] The catalyst composition as described in [5], wherein L in the aforementioned formula (1) is titanium (Ti).

[0042] [7] The catalyst composition as described in any one of [1] to [5], wherein the aforementioned catalyst additive is at least one selected from the group consisting of Fe, Ni, Al, Ti, TiSi, TiO, TiN and TiC.

[0043] [8] The catalyst composition as described in any one of [1] to [7], wherein, in the aforementioned formula (2), M represents one or more selected from the group consisting of barium (Ba), cerium (Ce), magnesium (Mg), calcium (Ca), strontium (Sr), lanthanum (La), silicon (Si) and aluminum (Al).

[0044] p is a value greater than or equal to 1, q is a value greater than or equal to 1, w is a value greater than or equal to 0, s is a value greater than or equal to 0, and t is a value greater than or equal to 0.

[0045] [9] The catalyst composition as described in any one of [1] to [7], wherein, in the aforementioned formula (2), M represents one or more selected from the group consisting of barium (Ba), cerium (Ce), magnesium (Mg), calcium (Ca), strontium (Sr), and lanthanum (La).

[0046] p is a value greater than or equal to 1, q is a value greater than or equal to 1, w is 0, s is 0, and t is 0.

[0047]

[10] The catalyst composition as described in any one of [1] to [9], wherein the catalyst substance represented by the aforementioned formula (2) is the catalyst substance represented by the following formula (2-1).

[0048] M p O q (2-1)

[0049] (In equation (2-1), M, p, q, w, s, and t have the same meaning as M, p, q, w, s, and t in the aforementioned equation (2).)

[0050]

[11] The catalyst composition as described in any one of [1] to

[11] , wherein the catalyst substance is selected from the group consisting of Ba-MgO, Sr-MgO, BaAl2O4, CeO2, and Ba-CeO2.

[0051]

[12] The catalyst composition as described in any one of [1] to

[11] , wherein the aforementioned chemical reaction catalyst further comprises a catalytically active metal,

[0052] The aforementioned chemical reaction catalyst is a metal-supported material obtained by supporting the aforementioned catalytically active metal on a support.

[0053] The aforementioned support is the aforementioned catalyst substance represented by the aforementioned formula (2).

[0054]

[13] The catalyst composition as described in

[12] , wherein the aforementioned catalytically active metal is at least one selected from the group consisting of ruthenium (Ru), cobalt (Co), iron (Fe), nickel (Ni), molybdenum (Mo), rhodium (Rh), rhenium (Re), chromium (Cr) and manganese (Mn).

[0055]

[14] The catalyst composition as described in

[12] or

[13] , wherein the aforementioned support does not simultaneously contain silicon (Si), oxygen (O) and aluminum (Al).

[0056]

[15] The catalyst composition as described in any one of

[12] to

[14] is characterized in that the aforementioned support is an alkaline metal oxide.

[0057]

[16] The catalyst composition as described in

[15] is characterized in that the aforementioned support is a crystalline alkaline metal oxide.

[0058]

[17] The catalyst composition as described in any one of [1] to [4], wherein, in the aforementioned formula (1), L is titanium (Ti),

[0059] In the aforementioned formula (2), M represents one or more elements selected from the group consisting of barium (Ba), cerium (Ce), magnesium (Mg), calcium (Ca), strontium (Sr), and lanthanum (La).

[0060] p represents a value greater than 1, q represents a value greater than 1.

[0061] The aforementioned chemical reaction catalysts also include catalytically active metals.

[0062] The aforementioned chemical reaction catalyst is a metal-supported material obtained by supporting the aforementioned catalytically active metal on a support.

[0063] The aforementioned support is the catalyst substance represented by formula (2) above.

[0064] The aforementioned catalytically active metal is selected from at least one of the following groups: ruthenium (Ru), cobalt (Co), and iron (Fe).

[0065]

[18] The catalyst composition as described in any one of [1] to [4], wherein the aforementioned catalyst additive is at least one selected from the group consisting of Ti, TiSi, TiO, TiN, and TiC.

[0066] The aforementioned catalyst is selected from one of the following groups: Ba-MgO, Sr-MgO, BaAl2O4, CeO2, and Ba-CeO2.

[0067] The aforementioned chemical reaction catalysts also include catalytically active metals.

[0068] The aforementioned chemical reaction catalyst is a metal-supported material obtained by supporting the aforementioned catalytically active metal on a support.

[0069] The aforementioned support is the aforementioned catalyst substance.

[0070] The aforementioned catalytically active metal is selected from one of the groups consisting of Ru, Co, and Fe.

[0071]

[19] A method for promoting catalytic activity, which is a method for promoting the catalytic activity of a catalyst for a chemical reaction by enhancing its electron-donating ability, the method comprising the steps of adding or mixing a catalyst additive into the catalyst or its precursor for a chemical reaction, characterized in that...

[0072] The process includes a step of reacting a mixture obtained by adding or mixing the aforementioned catalyst additive into a chemical reaction catalyst or its precursor at a temperature below 700°C in the presence of a reducing gas or an inactive gas.

[0073] The aforementioned catalyst additive is the catalyst additive represented by the following formula (1).

[0074] The aforementioned chemical reaction catalyst is a chemical reaction catalyst containing a catalyst substance represented by the following formula (2).

[0075] L m A n (1)

[0076] (In formula (1),)

[0077] L indicates that at least one element is selected from the group consisting of free transition elements and aluminum (Al).

[0078] A represents at least one element selected from the group consisting of silicon (Si), oxygen (O), nitrogen (N), and carbon (C).

[0079] (m represents a value greater than 1, and n represents a value greater than 0.)

[0080] M p O q C w N s H t (2)

[0081] (In formula (2),)

[0082] M indicates that one or more elements are selected from the group consisting of typical elements and transitional elements.

[0083] p represents a value greater than 1, q represents a value greater than 0, w represents a value greater than 0, s represents a value greater than 0, and t represents a value greater than 0. Note that q, w, s, and t cannot all be 0 simultaneously.

[0084]

[20] The catalytic activity enhancement method as described in

[19] , wherein the aforementioned temperature conditions are below 600°C.

[0085]

[21] The catalytic activity enhancement method as described in

[19] or

[20] , wherein the aforementioned chemical reaction catalyst further comprises a catalytically active metal,

[0086] The aforementioned chemical reaction catalyst is a metal-supported material obtained by supporting the aforementioned catalytically active metal on a support.

[0087] The aforementioned support is the aforementioned catalyst substance represented by the aforementioned formula (2).

[0088]

[22] The catalytic activity promotion method as described in any one of

[19] to

[21] , wherein the aforementioned catalytic activity is hydrogenation reaction activity.

[0089]

[23] The catalytic activity promotion method as described in

[22] , wherein the aforementioned hydrogenation reaction activity is ammonia synthesis activity.

[0090]

[24] The catalytic activity enhancement method as described in any one of

[19] to

[23] , wherein the aforementioned catalyst additive does not have hydrogenation reaction activity.

[0091]

[25] A method for manufacturing a catalyst composition, wherein the catalyst composition described in [1] to

[18] is manufactured, the method comprising the following steps:

[0092] The first step involves mixing the aforementioned catalyst additive with the aforementioned chemical reaction catalyst or its precursor; and

[0093] The second step involves reacting the first mixture obtained in the first step at a temperature below 700°C in the presence of a reducing gas or an inactive gas.

[0094]

[26] A method for manufacturing a catalyst composition, wherein the method comprises the following steps:

[0095] The first step involves mixing the catalyst additive with the chemical reaction catalyst or its precursor; and

[0096] The second step involves reacting the first mixture obtained in the first step at a temperature below 700°C in the presence of a reducing gas or an inert gas.

[0097] The aforementioned catalyst additive is the catalyst additive represented by the following formula (1).

[0098] The aforementioned chemical reaction catalyst is a chemical reaction catalyst containing a catalyst substance represented by the following formula (2).

[0099] L m A n (1)

[0100] (In formula (1),)

[0101] L indicates that at least one element is selected from the group consisting of free transition elements and aluminum (Al).

[0102] A represents at least one element selected from the group consisting of silicon (Si), oxygen (O), nitrogen (N), and carbon (C).

[0103] (m represents a value greater than 1, and n represents a value greater than 0.)

[0104] M p O q C w N s H t (2)

[0105] (In formula (2),)

[0106] M indicates that one or more elements are selected from the group consisting of typical elements and transitional elements.

[0107] p represents a value greater than 1, q represents a value greater than 0, w represents a value greater than 0, s represents a value greater than 0, and t represents a value greater than 0. Note that q, w, s, and t cannot all be 0 simultaneously.

[0108]

[27] A method for manufacturing a catalyst composition as described in

[25] or

[26] , wherein the aforementioned temperature conditions are below 600°C.

[0109]

[28] The method for manufacturing the catalyst composition as described in any one of

[25] to

[27] further includes a third step of obtaining the catalyst composition by using the second mixture obtained in the second step without removing the catalyst additive contained in the second mixture.

[0110]

[29] The method for manufacturing the catalyst composition as described in any one of

[25] to

[28] further includes a third step of using the second mixture obtained in the second step and removing the catalyst additive contained in the second mixture.

[0111]

[30] A catalyst composition obtained by any one of the methods described in

[26] to

[29] .

[0112]

[31] A method for manufacturing hydrides, characterized in that it includes a step of reacting the raw material compound to be hydrogenated with hydrogen in the presence of any one of the catalyst compositions described in [1] to

[18] and

[30] .

[0113]

[32] A method for producing ammonia, characterized in that it includes a step of reacting nitrogen with hydrogen in the presence of any one of the catalyst compositions described in [1] to

[18] and

[30] .

[0114]

[33] The catalyst additive represented by the following formula (1) is used in the following reaction, which is a reaction in which a mixture obtained by adding or mixing the catalyst additive to a chemical reaction catalyst or its precursor is carried out at a temperature below 700°C and in the presence of a reducing gas or an inactive gas in a catalytic activity promoting reaction, which promotes the electron-donating ability of the chemical reaction catalyst and thus promotes catalytic activity.

[0115] L m A n (1)

[0116] (In formula (1),)

[0117] L indicates that at least one element is selected from the group consisting of free transition elements and aluminum (Al).

[0118] A represents at least one element selected from the group consisting of silicon (Si), oxygen (O), nitrogen (N), and carbon (C).

[0119] (m represents a value greater than 1, and n represents a value greater than 0.)

[0120] Invention Effects

[0121] The catalyst composition of the present invention can improve catalyst performance by adding catalyst additives. Furthermore, the catalyst composition of one embodiment of the present invention exhibits high ammonia synthesis activity when used as a hydrogenation catalyst, particularly as a catalyst for ammonia synthesis. Attached Figure Description

[0122] [ Figure 1 [Graph showing the dependence of TiSi addition amount on the catalytic activity (ammonia synthesis rate) of the catalyst compositions (ammonia synthesis catalysts) of Examples 1-5 and Comparative Example 1 (top reaction conditions (▲): 400°C, 0.9 MPa; bottom reaction conditions (△): 340°C, 0.9 MPa).

[0123] [ Figure 2 [Graph showing the catalytic activity (ammonia synthesis rate) of the catalyst composition (ammonia synthesis catalyst) in Examples 1, 6 and Comparative Example 1, catalytic activity (reaction conditions: 400°C, 0.9 MPa).]

[0124] [ Figure 3 [Graph showing the catalytic activity (ammonia synthesis rate) of the catalyst composition (ammonia synthesis catalyst) in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3.]

[0125] [ Figure 4 [Graph showing the catalytic activity (ammonia synthesis rate) of the catalyst compositions (ammonia synthesis catalysts) in Examples 1 and 7-11, and Comparative Examples 1, 2 and 4-7.]

[0126] [ Figure 5 [Graph showing the catalytic activity (ammonia synthesis rate) of the catalyst compositions (ammonia synthesis catalysts) of Examples 1, 12-19 and Comparative Example 1 (reaction conditions: 400°C, 0.9 MPa).

[0127] [ Figure 6 [Graph showing the catalytic activity (ammonia synthesis rate) of the catalyst compositions (ammonia synthesis catalysts) of Examples 1, 12-18 and Comparative Example 1 (reaction conditions: 340°C, 0.9 MPa).

[0128] [ Figure 7 [A graph showing the change in catalytic activity (ammonia synthesis rate) over time in Example 1 (reaction conditions: 400°C, 0.9 MPa).] Detailed Implementation

[0129] (Terminology Explanation)

[0130] In this invention, the term "hydrogenation reaction activity" refers to catalytic activity in the context of hydrogenation reactions. Furthermore, the terms "catalyst with hydrogenation reaction activity" and "hydrogenation reaction catalyst" refer to catalysts with catalytic activity in the context of hydrogenation reactions. Hydrogenation is a reduction reaction in which hydrogen gas is used as a reducing agent to add hydrogen atoms to a compound. The "hydrogenation reaction" in this invention specifically refers to hydrogenation reactions using a catalyst, also known as "catalytic hydrogenation."

[0131] In this invention, the term "ammonia synthesis activity" refers to catalytic activity in the ammonia synthesis reaction, a specific example of a hydrogenation reaction. Furthermore, the terms "catalyst with ammonia synthesis activity" and "ammonia synthesis catalyst" refer to catalysts that exhibit catalytic activity in the ammonia synthesis reaction.

[0132] In this invention, the statement that "catalyst A has a higher hydrogenation reaction activity than catalyst B" means that, under the same reaction conditions except for the type of catalyst, catalyst A has a higher hydrogenation reaction rate than catalyst B.

[0133] In this invention, the term "catalytically active metal" refers to a metal that exhibits catalytic activity for a specific chemical reaction. For example, in the case of hydrogenation reactions such as ammonia synthesis, a catalytically active metal is a metal that exhibits hydrogenation reaction activity, such as ammonia synthesis activity, for hydrogenation reactions like ammonia synthesis.

[0134] In this invention, the term "precursor to a chemical reaction catalyst" refers to a raw material or intermediate product used to manufacture a chemical reaction catalyst. When the raw material or intermediate product contains two compounds, the precursor to the chemical reaction catalyst can also be a mixture. For example, in the specific example of Example 1, a mixture of raw materials formed from "MgO + Ba(NO3)2 + Ru(NO)(NO3)3" is a Ru / Ba-MgO precursor used as a chemical reaction catalyst.

[0135] (Catalyst Composition)

[0136] The catalyst composition of this embodiment includes a catalyst additive represented by formula (1) below and a chemical reaction catalyst containing a catalyst substance represented by formula (2) below.

[0137] L m A n (1)

[0138] (In formula (1), L represents at least one element selected from the group consisting of a free transition element and aluminum (Al).)

[0139] A represents at least one element selected from the group consisting of silicon (Si), oxygen (O), nitrogen (N), and carbon (C).

[0140] (m represents a value greater than 1, and n represents a value greater than 0.)

[0141] M p O q C w N s H t (2)

[0142] In equation (2), M represents one or more elements selected from a group consisting of typical elements and transition elements, wherein M does not simultaneously include aluminum (Al) and calcium (Ca).

[0143] p represents a value greater than 1, q represents a value greater than 0, w represents a value greater than 0, s represents a value greater than 0, and t represents a value greater than 0. Note that q, w, s, and t cannot all be 0 simultaneously.

[0144] The catalyst composition described above is not particularly limited. For example, the catalyst composition of the first embodiment and the catalyst composition of the second embodiment can be cited below.

[0145] <First Implementation Method>

[0146] The catalyst composition and chemical reaction catalyst of this embodiment have hydrogenation reaction activity. That is, the catalyst composition and chemical reaction catalyst of this embodiment are hydrogenation reaction catalysts.

[0147] Preferably, the hydrogenation reaction activity of the aforementioned catalyst composition is higher than that of the aforementioned chemical reaction catalyst.

[0148] The hydrogenation reaction activity of the catalyst composition and the chemical reaction catalyst in this embodiment is preferably ammonia synthesis activity.

[0149] The catalyst additives contained in the catalyst composition of this embodiment may have hydrogenation reaction activity, or they may not have hydrogenation reaction activity.

[0150] [Catalyst Additives]

[0151] In the catalyst additives involved in this embodiment, the transition element used for L in formula (1) is not particularly limited, and is usually a transition element of group 3, 4, 5, 6, 7, 8, 9, 10 or 11 of the periodic table, preferably a transition element of group 4, 8 or 10, and more preferably a group 4 element.

[0152] For the catalyst additive involved in this embodiment, in the aforementioned formula (1), L is preferably selected from at least one of the group consisting of titanium (Ti), iron (Fe), nickel (Ni) and aluminum (Al), and L is more preferably titanium (Ti).

[0153] The aforementioned catalyst additive is preferably at least one selected from the group consisting of Fe, Ni, Al, Ti, TiSi, TiO, TiN, and TiC. More preferably, the aforementioned catalyst additive is at least one selected from the group consisting of Ti, TiSi, TiO, TiN, and TiC. Even more preferably, the aforementioned catalyst additive is Ti.

[0154] Titanium silicides are titanium silicides that are alloys of titanium and silicon. They possess an internal structure composed of TiSi and TiSi2. Unless otherwise specified, the term "titanium silicide" refers specifically to TiSi. Additionally, titanium silicides are sometimes also called TiSix. In this invention, unless otherwise specified, "TiSi" and "TiSix" are used interchangeably.

[0155] The catalyst additive involved in this embodiment may not have hydrogenation reaction activity. Additionally, the catalyst additive involved in this embodiment may not have ammonia synthesis activity.

[0156] Examples of catalyst additives that do not have ammonia synthesis activity include Al, Ti, TiSi, TiO, TiN, or TiC.

[0157] The catalyst additive involved in this embodiment can have hydrogenation reaction activity. Additionally, the catalyst additive involved in this embodiment can also have ammonia synthesis activity.

[0158] Examples of catalyst additives with ammonia synthesis activity include Fe and Ni.

[0159] When adding a catalyst additive with ammonia synthesis activity, it is preferable that the chemical reaction catalyst described later does not contain the same substance as the catalyst additive. For example, if the catalyst additive is Fe, it is preferable that the chemical reaction catalyst does not contain Fe.

[0160] The amount of catalyst additive involved in this embodiment refers to the content of catalyst additive relative to 100% by mass of the final catalyst composition. Preferably, it is 1% by mass or more, more preferably 5% by mass or more, and even more preferably 20% by mass or more. Preferably, it is 60% by mass or less, more preferably 50% by mass or less, and even more preferably 45.0% by mass or less.

[0161] This embodiment includes the use of a catalyst additive represented by the following formula (1) for a reaction in which a mixture obtained by adding or mixing the catalyst additive to a chemical reaction catalyst or its precursor is carried out at a temperature below 700°C and in the presence of a reducing gas or an inactive gas in a catalytic activity promoting reaction, wherein the catalytic activity promoting reaction promotes the electron-donating ability of the chemical reaction catalyst, thereby promoting catalytic activity.

[0162] L m A n (1)

[0163] (In formula (1),)

[0164] L indicates that at least one element is selected from the group consisting of free transition elements and aluminum (Al).

[0165] A represents at least one element selected from the group consisting of silicon (Si), oxygen (O), nitrogen (N), and carbon (C).

[0166] (m represents a value greater than 1, and n represents a value greater than 0.)

[0167] In the above embodiments, the above-described catalyst additives are used to promote the catalytic activity of the reaction, thereby improving the catalytic performance of the catalyst composition of the present invention. Therefore, it is expected that the instability of the chemical reaction catalyst contained in the catalyst composition of the present invention will be suppressed, and the load on the reaction apparatus based on high-temperature hydrogen treatment will be reduced.

[0168] [Chemical reaction catalyst]

[0169] The chemical reaction catalyst involved in the first embodiment further comprises a catalytically active metal. That is, the chemical reaction catalyst involved in this embodiment is a metal support obtained by supporting the aforementioned catalytically active metal on a support. The aforementioned support is the aforementioned catalyst material represented by the aforementioned formula (2).

[0170] <<Catalytically Active Metals>>

[0171] The catalytically active metal involved in this embodiment is preferably a transition metal.

[0172] The transition metals used in this embodiment are not particularly limited, and are usually transition metals from Group 6, 7, 8, 9 or 10 of the periodic table. They are preferably transition metals from Group 6, 8 or 9, and more preferably metals from Group 8 or 9.

[0173] The catalytically active metal involved in this embodiment is preferably at least one selected from the group consisting of ruthenium (Ru), cobalt (Co), iron (Fe), nickel (Ni), molybdenum (Mo), rhodium (Rh), rhenium (Re), chromium (Cr), and manganese (Mn). More preferably, the catalytically active metal involved in this embodiment is at least one selected from the group consisting of ruthenium (Ru), cobalt (Co), iron (Fe), and nickel (Ni). Even more preferably, the catalytically active metal involved in this embodiment is ruthenium (Ru).

[0174] The aforementioned elements can be used individually or in combination of two or more. Additionally, intermetallic compounds of these elements, such as Co3Mo3N, Fe3Mo3N, Ni2Mo3N, and Mo2N, can also be used. It is preferable to use each element individually or in combination of two or more, and even more preferable to use them individually, which is advantageous in terms of cost.

[0175] <<Catalyst Material (Supporter)>>

[0176] For the catalyst material (support) involved in this embodiment, it is preferred that, in the aforementioned formula (2), M represents one or more selected from the group consisting of barium (Ba), cerium (Ce), magnesium (Mg), calcium (Ca), strontium (Sr), lanthanum (La), silicon (Si) and aluminum (Al).

[0177] p is a value greater than or equal to 1, q is a value greater than or equal to 1, w is a value greater than or equal to 0, s is a value greater than or equal to 0, and t is a value greater than or equal to 0.

[0178] For the catalyst material (support) involved in this embodiment, more preferably, in the aforementioned formula (2), M represents one or more selected from the group consisting of barium (Ba), cerium (Ce), magnesium (Mg), calcium (Ca), strontium (Sr) and lanthanum (La), p is a value of 1 or more, q is a value of 1 or more, w is 0, s is 0, and t is 0.

[0179] The catalyst material (support) involved in this embodiment is preferably an alkaline metal oxide, and more preferably a crystalline alkaline metal oxide.

[0180] Examples of alkaline metal oxides include BaO, SrO, MgO, CaO, CeO2, La2O3, Y2O3, and BaAl2O4.

[0181] The catalyst material (support) involved in this embodiment is more preferably the catalyst material represented by the following formula (2-1).

[0182] M p O q (2-1)

[0183] In equation (2-1), M represents one or more elements selected from a group consisting of typical elements and transition elements, wherein M does not simultaneously include aluminum (Al) and calcium (Ca). Furthermore, preferably, p represents a value greater than 0, q represents a value greater than 0, w represents a value greater than 0, s represents a value greater than 0, and t represents a value greater than 0.

[0184] "Compounds of Formula (2-1)"

[0185] The compounds of the above formula (2-1) can also be oxides of typical elements represented by the following general formula (2-1a).

[0186] A n B m O l (2-1a)

[0187] In the aforementioned general formula (2-1a), A is at least one selected from the group consisting of Ba and Sr, B is at least one selected from the group consisting of Al, Ga, In, Si, Ge and Sn, n is an integer from 1 to 17, m is an integer from 1 to 17, and l represents a number represented by an integer from 1 to 26. l is preferably 4 or 5.

[0188] It should be noted that the "typical element" involved in this embodiment refers to elements in Groups 1, 2, 12 to 18 of the periodic table. That is, it does not refer to transition elements in Groups 3 to 11 of the periodic table. The "typical element oxide" or "typical element complex oxide" involved in this invention preferably contains 90% by mass or more of an oxide or complex oxide formed from typical elements (elements in Groups 1, 2, 12 to 18 of the periodic table) excluding oxygen and oxygen. More preferably, it contains 95% by mass or more, 99% by mass or more, or substantially 100% by mass. Even more preferably, it contains substantially 100% by mass. The term "substantially contains 100% by mass" means, for example, that the content of the transition element is less than 1% by mass or less than 0.5% by mass.

[0189] The carrier of the metal support of the present invention preferably contains 50% by mass or more of the typical element oxide or "typical element composite oxide" involved in the present invention. More preferably, it contains 70% by mass or more. Further preferably, it contains 90% by mass or more. Particularly preferably, it contains substantially 100% by mass or more. The term "substantially contains 100% by mass" means, for example, that the content of the transition element oxide is less than 1% by mass or less than 0.5% by mass when calculated based on transition elements.

[0190] Specific examples of typical elemental oxides used in this embodiment include, for example, BaAl2O4, Ba3Al2O6, Ba4Al2O7, and Ba... 17Al3O7, BaAl4O7, BaAl 12 O 19 , BaGa2O4, BaGa4O7, Ba4Ga2O7, Ba3Ga2O6, BaInO 2.5 Ba3In2O6, Ba8In6O 17 , Ba2In2O5, Ba4In2O7, Ba4In6O 13 SrAl2O4, SrAl 12 O 19 SrAl4O7, Sr4Al 14 O 25 Sr9Al6O 18 Sr3Al2O6, Sr 10 Al6O 19 Sr2Al6O 11 、Sr7Al 12 O 25 SrGa2O4, Sr3Ga4O9, SrGa 12 O 19 、Sr 10 Ga6O 19 , Sr3Ga2O6, Sr4Ga2O7, Sr2Ga2O5, Sr5Ga6O 14 , SrGa4O7, Ba3SiO5, Ba2SiO4, Ba2Si4O 10 Ba4Si6O 16 BaSi4O9, Ba5Si8O 21 Ba6Si 10 O 26 , BaSiO3, BaSi2O5, Ba3GeO, BaGe4O9, BaGe2O5, Ba 10 Ge7O3, BaGeO3, Ba3Ge3O9, Sr3SiO5, Sr3Si3O9, Sr4Si4O 12 Examples of suitable materials include Sr₂SiO₄, SrSiO₃, SrSi₂O₅, Sr₃SiO, Sr₃GeO, Sr₂GeO₄, SrGeO₃, SrGe₄O₉, and SrGe₂O₅. Among these, BaAl₂O₄, Ba₂SiO₄, and Ba₃SiO₅ are preferred from the viewpoints of availability, ease of preparation, and versatility, with BaAl₂O₄ being even more preferred.

[0191] [Preparation methods for typical element oxides]

[0192] Examples of the synthesis of BaAl2O4 and Ba2SiO4 will be used for illustration.

[0193] <Synthesis of BaAl₂O₄>

[0194] 0.148 g of barium carbonate (Wako Pure Chemical Corporation, 99.9%) and 0.117 g of aluminum hydroxide (Kojundo Chemical Laboratory Co., Ltd., 99.99%) were mixed at a molar ratio of 1:2. The resulting mixture was charged into an alumina crucible, heated to 1000°C over 3 hours, and maintained at this temperature for 10 hours, thereby obtaining BaAl₂O₄.

[0195] <Synthesis of Ba₂SiO₄>

[0196] Using ethylene glycol (Kanto Chemical Co., Inc.·Wako Pure Chemical Corporation, 99.0%) with pre-dissolved citric acid (Kanto Chemical Co., Inc., 99.0%) as a solvent, Ba(CH₃COO)₂ (Kanto Chemical Co., Inc., 99.0%) was reacted with TEOS (tetraethyl orthosilicate) via a complex polymerization method. A stoichiometric amount of the obtained reactant (raw material for Ba₂SiO₄) was prepared, then charged into a beaker together with a stirring bar using ethylene glycol with pre-dissolved citric acid as the solvent, and stirred overnight at 120°C. Subsequently, the temperature was raised to 180°C and maintained for 6 hours, thereby obtaining a brown gel. Then, the obtained gel together with the beaker was transferred into a mantle heater and maintained at 450°C for 2 hours, thereby obtaining a black powder. The obtained black powder was charged into an alumina crucible and heated to 800°C over 40 minutes using an electric furnace, then maintained at 800°C for 4 hours, thereby obtaining the target white powder Ba₂SiO₄.

[0197] <Group 13 Main Group Element Oxides>

[0198] The main group element oxide according to the present embodiment may also be a composite oxide of a main group element represented by the following general formula (2-1b).

[0199] AB₂Oₗ l (2-1b)

[0200] (In the foregoing general formula (2-1b), B is at least one selected from the group consisting of Al, Ga, and In, l represents a number satisfying 3.5≤l≤4.5, and A has the same definition as A in general formula (1).)

[0201] The compound represented by the above general formula (2-1b) is a compound represented by the above general formula (2-1a) where n is 1, m is 2, l is a number satisfying 3.5≤l≤4.5, and B is at least one selected from the group consisting of Al, Ga, and In.

[0202] In the foregoing general formula (2), l preferably represents a number satisfying 3.8≤l≤4.2, more preferably represents a number satisfying 3.9≤l≤4.1, and still more preferably l is 4.

[0203] For example, commercially available BaAl2O4 prepared using the methods described in this application can be used.

[0204] <Oxides of typical elements containing Group 14 elements>

[0205] The typical element oxides in this embodiment are those represented by the following general formula (2-1c).

[0206] A2BO l (2-1c)

[0207] (In the aforementioned general formula (3), B is at least one of the groups composed of Si, Ge and Sn, l represents the number represented by 3.5≤l≤4.5, and the meaning of A is the same as that of A in general formula (2-1a).)

[0208] The compound represented by the above general formula (2-1c) is the compound represented by the above general formula (2-1a) in which n is 2, m is 1, l represents the number represented by 3.5≤l≤4.5, and B is a compound selected from at least one of the group consisting of Si, Ge and Sn.

[0209] In the aforementioned general formula (2-1c), l preferably represents the number represented by 3.8≤l≤4.2, more preferably the number represented by 3.9≤l≤4.1, and l is more preferably 4.

[0210] The compound of formula (2-1) above can also be a composite oxide represented by the following general formula (2-1d).

[0211] A n X y M m O x (2-1d)

[0212] (In the aforementioned general formula (2-1d), A is a rare earth element, characterized in that at least some or all of it is in a state of III valence.)

[0213] X is any element from Group 2, Group 4, or rare earth elements in the periodic table, and represents an element different from A mentioned above.

[0214] M is any element from Group 2, Group 4, or rare earth elements of the periodic table, and represents an element different from A and X mentioned above.

[0215] Regarding n, 0 <n<1,

[0216] y is 1-n,

[0217] Regarding m, 0 ≤ m ≤ 0.5,

[0218] x represents the number of oxygen atoms required for the composite oxide to maintain electrical neutrality.

[0219] As such an element A, lanthanide elements can be mentioned, preferably Ce, Pr, Tb, La. More preferably Ce or La, and most preferably Ce.

[0220] The element X constituting the composite oxide of general formula (2-1d) can be selected from, for example, Group 2 elements of the periodic table such as Mg, Ca, Sr, Ba, Group 4 elements such as Ti, Zr or Hf, or rare earth elements such as Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb or Lu. It is different from the other element A constituting the composite oxide, and X is different from M. When the element M is a Group 2 element of the periodic table, it is preferably selected from Ca, Sr and Ba. In addition, when the element M is a rare earth element, it is preferably a lanthanide element.

[0221] The element M constituting the composite oxide of general formula (2-1d) can be selected from, for example, Group 1 elements of the periodic table such as Na, K, Rb, Cs, Fr, Group 2 elements of the periodic table such as Mg, Ca, Sr, Ba, Group 4 elements such as Ti, Zr or Hf, or rare earth elements such as Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb or Lu. It is different from the other element A constituting the composite oxide, and M is different from X. When the element X is a Group 2 element of the periodic table, it is preferably selected from Ca, Sr and Ba. In addition, when the element X is a rare earth element, it is preferably a lanthanide element. Especially from the viewpoint of ammonia synthesis activity, the element M is preferably Ba.

[0222] Preferably, X and M are selected from Zr and La. In the composite oxide of the present invention, two Group 4 elements or rare earth elements of the periodic table may be included as X and M, or only one Group 4 element or rare earth element of the periodic table may be included as X (m=0 in general formula (2-1d)).

[0223] When the composite oxide of the present invention is represented by general formula (2-1d), the ranges of n, y, m and x are as described below.

[0224] Regarding n in general formula (2-1d), which represents the proportion of element A in the composite oxide, 0<n<1, preferably 0.05<n<0.95, more preferably 0.1<n<0.9, and particularly preferably 0.35≤n≤0.5.

[0225] Regarding y in general formula (2-1d) representing the proportion of element X in the composite oxide, 0<y<1, preferably 0.05<y<0.95, more preferably 0.1<y<0.9, and particularly preferably 0.35≤y≤0.5.

[0226] Regarding m in general formula (2-1d) representing the proportion of element M in the composite oxide, 0≤m<1; regarding m in general formula (2), 0≤m≤0.5. For both formula (1) and formula (2), 0<m<0.5 is preferred, 0.05≤m≤0.45 is more preferred, and 0.1≤m≤0.3 is particularly preferred. When m=0, the composite oxide is composed only of A, X and O.

[0227] For example, La 0.5 Ce 0.5 O 1.75 In the case of such a binary support containing two metal elements, which is a composite of lanthanide elements, a uniformly solid-solved solid solution is often formed. Moreover, Ru particles are in direct contact with the surface of the support. When Ce is reduced, both La and Ce are elements exhibiting strong alkalinity in the oxide state, so it is speculated that there are more active sites for Ru, leading to higher ammonia synthesis activity.

[0228] On the other hand, for example, Ba 0.1 La 0.45 Ce 0.45 O x In the case of such a ternary support containing three metal elements, the atomic radius of Ba is larger than that of La and Ce. In this case, when the firing temperature of the raw material mixture is high, for example, when the firing temperature is higher than 1000°C, all elements are uniformly solid-solved to form a perovskite-type crystal structure. On the other hand, when the firing temperature of the raw material mixture is low, since Ba is a large element, it is difficult to easily form a solid solution with other elements. Therefore, the structure is in a state where Ba is unevenly mixed in the solid solution formed by solid dissolution of La and Ce, and a part of Ba is exposed on the surface of the solid solution of La and Ce. Ba is a strongly alkaline element with a higher partial negative charge of oxygen than La and Ce, therefore, in the support with Ba exposed unevenly, the contact area between Ba and Ru increases, resulting in more active sites. Therefore, it is speculated that the ammonia synthesis activity becomes higher.

[0229] Specific examples of the composite oxide according to the present embodiment are given below.

[0230] Ce 0.5 La 0.5 O x

[0231] Pr 0.5 La 0.5 Ox

[0232] Ba 0.3 Pr 0.35 Ce 0.35 O x

[0233] Ba 0.1 La 0.45 Ce 0.45 O x

[0234] <Methods for Manufacturing Metal Oxides and Metal Supports>

[0235] The composite oxide of this embodiment can be manufactured using the following method.

[0236] Includes the following processes:

[0237] (a) A mixing process, wherein a precursor A containing element A, a precursor X containing element X, and a precursor M containing element M are mixed to obtain a mixture; and

[0238] (b) Firing process, wherein the mixture is fired.

[0239] The above-described specific example of the composite oxide of this embodiment can be synthesized using the same method as that disclosed in the embodiments of Patent Document 7.

[0240] Examples of catalyst materials (supports) involved in this embodiment include Ba-MgO, Sr-MgO, BaAl2O4, CeO2, and Ba-CeO2. Among them, Ba-MgO, BaAl2O4, CeO2, and Ba-CeO2 are preferred.

[0241] Preferably, the catalyst material (support) involved in this embodiment does not simultaneously contain silicon (Si), oxygen (O) and aluminum (Al).

[0242] <<Metal Supports>>

[0243] The metal support in this embodiment is obtained by supporting a transition metal (M) on the above-mentioned catalyst material (support). The aforementioned transition metal (M) is preferably at least one selected from the group consisting of Ru, Co, and Fe.

[0244] The loading amount of the aforementioned transition metal is not particularly limited, but generally, it is 0.01 parts by mass (0.01% by mass) or more relative to 100 parts by mass of the aforementioned carrier, preferably 0.5 parts by mass (0.5% by mass) or more, more preferably 1 part by mass (1% by mass) or more, further preferably 2 parts by mass (2% by mass) or more, generally 50 parts by mass (50% by mass) or less, preferably 30 parts by mass (30% by mass) or less, more preferably 20 parts by mass (20% by mass) or less, further preferably 10 parts by mass (10% by mass) or less. If it is above the aforementioned lower limit, the effects of the present invention can be obtained; if it is below the aforementioned upper limit, the effects of the present invention, which balance the loading amount and cost, can be obtained.

[0245] <Methods for loading transition metals (M) onto metallic supports>

[0246] There is no particular limitation on the method of loading transition metal (M) onto a metal support. For example, a support on which a transition metal (M) is immobilized on a catalyst material (support) can be obtained by the following method. As an example of the above method, a method including the following steps can be given: dispersing the aforementioned catalyst material (support) and the precursor of the metal to be supported in an aqueous solution and stirring; drying the resulting mixture at 140°C for about 2 hours after stirring; and then heating the dried product at 400°C for 4 hours under a nitrogen atmosphere to thermally decompose the metal compound.

[0247] For example, transition metal compounds with transition metals (M) of Ru, Co, and Fe can include nitrates, formates, and carbonyl complexes. Specifically, for example, Ru(NO)(NO3)3, Co(NO3)2, and Fe(NO3)3 can be used to synthesize Ru-supported compounds (referred to as Ru / support), Co-supported compounds (referred to as Co / support), and Fe-supported compounds (referred to as Fe / support).

[0248] <Shape of the metal support>

[0249] The shape of the metal support in this embodiment is not particularly limited. Specifically, it can be any shape, such as block, powder, or film, but is usually powder. The particle size of the powdered metal support is not particularly limited, but is usually 1 nm or more and 10 μm or less.

[0250] The particle size of the transition metal in the metal support of this embodiment is not particularly limited, and is generally 1 nm or more and 100 nm or less. From the perspective of increasing the number of step sites as active sites for nitrogen dissociation when used as a catalyst for ammonia synthesis, it is preferable to be 20 nm or less, and more preferably 10 nm or less.

[0251] Examples of catalyst compositions used in this embodiment include ammonia synthesis catalysts, wherein...

[0252] The catalyst additive involved in this embodiment is selected from at least one of the group consisting of Ti, TiSi, TiO, TiN, and TiC.

[0253] The catalyst involved in this embodiment is selected from one of the following groups: Ba-MgO, Sr-MgO, BaAl2O4, CeO2, and Ba-CeO2.

[0254] The chemical reaction catalyst involved in this embodiment also includes a catalytically active metal.

[0255] The aforementioned chemical reaction catalyst is a metal-supported material obtained by supporting the aforementioned catalytically active metal on a support.

[0256] The aforementioned support is the aforementioned catalyst substance.

[0257] The aforementioned catalytically active metal is selected from one of the groups consisting of Ru, Co, and Fe.

[0258] Furthermore, as a catalyst composition in this embodiment, an ammonia synthesis catalyst can be cited, wherein...

[0259] The catalyst additive involved in this embodiment is selected from at least one of the group consisting of Ti, TiSi, TiO, TiN, and TiC.

[0260] The catalyst involved in this embodiment is selected from one of the following groups: Ba-MgO, BaAl2O4, CeO2, and Ba-CeO2.

[0261] The chemical reaction catalyst involved in this embodiment also includes a catalytically active metal.

[0262] The aforementioned chemical reaction catalyst is a metal-supported material obtained by supporting the aforementioned catalytically active metal on a support.

[0263] The aforementioned support is the aforementioned catalyst substance.

[0264] The aforementioned catalytically active metal is selected from one of the groups consisting of Ru, Co, and Fe.

[0265] <Second Implementation Method>

[0266] The catalyst composition of this embodiment can use the same substances as the catalyst additives and catalyst substances described in the first embodiment. Various embodiments, preferred examples, manufacturing methods, etc., related to the aforementioned catalyst additives and catalyst substances in the first embodiment are referenced in this embodiment.

[0267] The catalyst composition of this embodiment differs from the chemical reaction catalyst of the first embodiment compared to the catalyst composition of the first embodiment. The chemical reaction catalyst of this embodiment differs from the chemical reaction catalyst of the first embodiment in that it does not contain a catalytically active metal. However, the chemical reaction catalyst of this embodiment is the same as that of the first embodiment, except that it does not contain a catalytically active metal. That is, the chemical reaction catalyst of this embodiment contains a catalyst material that does not support a catalytically active metal. The catalyst material of this embodiment is the same as that of the catalyst material of the first embodiment.

[0268] The chemical reaction catalyst involved in this embodiment may, as needed, also include substances other than the aforementioned catalyst substances (excluding catalytically active metals). The chemical reaction catalyst of this embodiment is preferably the catalyst substance of this embodiment.

[0269] Examples of catalyst compositions used in this embodiment include ammonia synthesis catalysts, wherein...

[0270] The catalyst additive involved in this embodiment is selected from at least one of the group consisting of Ti, TiSi, TiO, TiN, and TiC.

[0271] The catalyst involved in this embodiment is selected from one of the following groups: Ba-MgO, Sr-MgO, BaAl2O4, CeO2, and Ba-CeO2.

[0272] The chemical reaction catalyst involved in this embodiment is a catalyst substance.

[0273] Furthermore, as a catalyst composition in this embodiment, an ammonia synthesis catalyst can be cited, wherein...

[0274] The catalyst additive involved in this embodiment is selected from at least one of the groups consisting of Ti, TiSi, TiO, TiN, and TiC, and the catalyst substance involved in this embodiment is selected from one of the groups consisting of Ba-MgO, BaAl2O4, CeO2, and Ba-CeO2.

[0275] The chemical reaction catalyst involved in this embodiment is the catalyst composition described above.

[0276] (Methods to enhance catalytic activity)

[0277] The catalytic activity enhancement method of this embodiment is a method for enhancing the catalytic activity by enhancing the electron-donating ability of the aforementioned chemical reaction catalyst. The catalytic activity enhancement method includes the step of adding or mixing a catalyst additive into the chemical reaction catalyst or its precursor.

[0278] A method for promoting catalytic activity, characterized by comprising a step of reacting a mixture obtained by adding or mixing the aforementioned catalyst additive into a chemical reaction catalyst or its precursor at a temperature below 700°C in the presence of a reducing gas or an inactive gas, and,

[0279] The aforementioned catalyst additive is the catalyst additive represented by the following formula (1).

[0280] The aforementioned chemical reaction catalyst is a chemical reaction catalyst containing a catalyst substance represented by the following formula (2).

[0281] L m A n (1)

[0282] (In formula (1),)

[0283] L indicates that at least one element is selected from the group consisting of free transition elements and aluminum (Al).

[0284] A represents at least one element selected from the group consisting of silicon (Si), oxygen (O), nitrogen (N), and carbon (C).

[0285] (m represents a value greater than 1, and n represents a value greater than 0.)

[0286] M p O q C w N s H t (2)

[0287] (In formula (2),)

[0288] M indicates that one or more elements are selected from the group consisting of typical elements and transitional elements.

[0289] p represents a value greater than 1, q represents a value greater than 0, w represents a value greater than 0, s represents a value greater than 0, and t represents a value greater than 0. Note that q, w, s, and t cannot all be 0 simultaneously.

[0290] The aforementioned temperature conditions are preferably below 600°C.

[0291] In the catalytic activity enhancement method of this embodiment, the aforementioned chemical reaction catalyst may include a catalyst substance and a catalytically active metal.

[0292] The aforementioned chemical reaction catalyst is a metal-supported material obtained by supporting the aforementioned catalytically active metal on a support.

[0293] The aforementioned support is the aforementioned catalyst substance represented by the aforementioned formula (2).

[0294] In the catalytic activity enhancement method of this embodiment, the aforementioned chemical reaction catalyst may not contain a catalytically active metal.

[0295] In the catalytic activity promotion method of this embodiment, the aforementioned catalytic activity is preferably hydrogenation reaction activity, and more preferably ammonia synthesis activity.

[0296] In the catalytic activity enhancement method of this embodiment, the aforementioned catalyst additive may or may not have hydrogenation reaction activity.

[0297] The preferred methods and specific examples of the catalyst additives and chemical reaction catalysts involved in this embodiment can be referred to the preferred methods and specific examples described in the first and second embodiments of the catalyst composition.

[0298] (Method for preparing the catalyst composition)

[0299] One embodiment of the manufacturing method of the present invention is a method for manufacturing the aforementioned catalyst composition. The manufacturing method of this embodiment includes the following steps:

[0300] The first step involves mixing the aforementioned catalyst additive with the aforementioned chemical reaction catalyst or its precursor; and

[0301] The second step involves reacting the first mixture obtained in the first step at a temperature below 700°C in the presence of a reducing gas or an inactive gas.

[0302] Other embodiments of the manufacturing method of the present invention include the following steps:

[0303] The first step involves mixing the catalyst additive with the chemical reaction catalyst or its precursor; and

[0304] The second step involves reacting the first mixture obtained in the first step at a temperature below 700°C in the presence of a reducing gas or an inactive gas.

[0305] The aforementioned catalyst additive is the catalyst additive represented by the following formula (1).

[0306] The aforementioned chemical reaction catalyst is a chemical reaction catalyst containing a catalyst substance represented by the following formula (2).

[0307] L m A n (1)

[0308] (In formula (1),)

[0309] L indicates that at least one element is selected from the group consisting of free transition elements and aluminum (Al).

[0310] A represents at least one element selected from the group consisting of silicon (Si), oxygen (O), nitrogen (N), and carbon (C).

[0311] (m represents a value greater than 1, and n represents a value greater than 0.)

[0312] M p O q C w N s H t (2)

[0313] (In formula (2),)

[0314] M indicates that one or more elements are selected from the group consisting of typical elements and transitional elements.

[0315] p represents a value greater than 1, q represents a value greater than 0, w represents a value greater than 0, s represents a value greater than 0, and t represents a value greater than 0. Note that q, w, s, and t cannot all be 0 simultaneously.

[0316] The aforementioned temperature conditions are preferably below 600°C. Alternatively, the aforementioned temperature conditions can be below 500°C.

[0317] The manufacturing method of this embodiment may further include a third step of obtaining the catalyst composition by using the second mixture obtained in the second step without removing the catalyst additive contained in the second mixture.

[0318] The manufacturing method of this embodiment may further include a third step of using the second mixture obtained in the aforementioned second step and removing the aforementioned catalyst additive contained in the second mixture. For such a manufacturing method, the aforementioned third step may result in the presence of a small amount of residual catalyst additive, or it may result in the presence of no catalyst additive at all. Here, "small amount" as used above refers, for example, to the presence of 1% to 5% by mass, 1% to 2.5% by mass, 1% to 2.0% by mass, or 1% to 1.5% by mass of residual catalyst additive.

[0319] Here, "not containing" means that, relative to 100% by mass of the catalyst composition, the content (amount) of the catalyst additive is 0% or more but less than 1% by mass, 0% to 0.5% by mass, or 0% to 0.25% by mass.

[0320] The preferred methods and specific examples of the manufacturing method of this embodiment involving catalyst additives and chemical reaction catalysts can be referred to the preferred methods and specific examples described in the first and second embodiments of the aforementioned catalyst composition.

[0321] (A method for producing compounds using a catalyst composition as a catalyst)

[0322] <Methods for manufacturing hydrides>

[0323] The method for producing hydrides according to this embodiment includes a step of reacting the raw material compound to be hydrogenated with hydrogen in the presence of the catalyst composition of this embodiment described above.

[0324] <Methods for manufacturing ammonia>

[0325] The ammonia manufacturing method of this embodiment is characterized by including a step of reacting nitrogen and hydrogen in the presence of the catalyst composition of this embodiment.

[0326] In this embodiment, the catalyst composition is an ammonia catalyst.

[0327] The ammonia manufacturing method of this embodiment (hereinafter, sometimes referred to as the manufacturing method of this embodiment) is a method of synthesizing ammonia by using the ammonia synthesis catalyst of this embodiment as a catalyst and reacting hydrogen and nitrogen on the aforementioned catalyst.

[0328] As for the specific manufacturing method, any method that brings hydrogen and nitrogen into contact on the aforementioned catalyst to synthesize ammonia is acceptable, without particular limitation, and can be manufactured according to known manufacturing methods.

[0329] In the ammonia production method of this embodiment, ammonia is typically produced by heating the catalyst while hydrogen and nitrogen are brought into contact on the aforementioned catalyst.

[0330] The reaction temperature in the manufacturing method of this embodiment is not particularly limited, but is generally 200°C or higher, preferably 250°C or higher, more preferably 300°C or higher, generally 600°C or lower, preferably 500°C or lower, and more preferably 450°C or lower. Ammonia synthesis is an exothermic reaction; therefore, a low temperature range is favorable for ammonia formation according to chemical equilibrium theory. However, to obtain a sufficient ammonia formation rate, the reaction is preferably carried out within the above-mentioned temperature range.

[0331] In the manufacturing method of this embodiment, the molar ratio of nitrogen to hydrogen in contact with the aforementioned catalyst is not particularly limited, and is generally carried out under conditions where the ratio of hydrogen to nitrogen (H2 / N2 (volume / volume)) is typically 0.4 or more, preferably 0.5 or more, more preferably 1 or more, typically 10 or less, and preferably 5 or less.

[0332] The reaction pressure in the manufacturing method of this embodiment is not particularly limited. Using a pressure gauge containing a mixture of nitrogen and hydrogen, it is typically 0.01 MPa or higher, preferably 0.1 MPa or higher, typically 20 MPa or lower, preferably 15 MPa or lower, and more preferably 10 MPa or lower. Furthermore, considering practical application, it is preferable to conduct the reaction under pressure conditions above atmospheric pressure.

[0333] In the manufacturing method of this embodiment, it is preferable to remove the moisture and oxides adhering to the catalyst by means of a dehydrating material, cryogenic separation, or hydrogen gas before contacting nitrogen and hydrogen with the catalyst. Reduction treatment is an example of such a removal method.

[0334] In the manufacturing method of this embodiment, in order to obtain a better ammonia yield, it is preferable that the nitrogen and hydrogen used in the manufacturing method of this embodiment have low moisture content. There is no particular limitation, but generally, the total moisture content in the nitrogen and hydrogen mixture is 100 ppm or less, preferably 50 ppm or less.

[0335] In the manufacturing method of this embodiment, the form of the reaction vessel is not particularly limited, and a reaction vessel commonly used in ammonia synthesis reactions can be used. As specific reaction forms, for example, batch reaction, closed-loop reaction, and flow-through reaction can be employed. From a practical point of view, a flow-through reaction is preferred. Alternatively, a reactor filled with a catalyst, a method of connecting multiple reactors, or a reactor having multiple reaction layers within the same reactor can also be used.

[0336] The reaction for synthesizing ammonia from hydrogen and nitrogen is an exothermic reaction accompanied by volume contraction. Therefore, in order to improve the ammonia yield, it is industrially preferable to remove the heat of reaction. Known reaction apparatuses with commonly used heat removal methods can also be used. Specifically, for example, methods such as connecting multiple reactors packed with catalyst in series and installing intercoolers at the outlets of each reactor can be used for heat removal.

[0337] In the ammonia production method of this embodiment, the ammonia synthesis catalyst obtained by the production method of this embodiment can be used alone, or it can be used in combination with other known catalysts that are commonly used in ammonia synthesis.

[0338] The preferred methods and specific examples of the catalyst composition involved in the manufacturing method of this embodiment can be referred to the preferred methods and specific examples described in the first and second embodiments of the catalyst composition.

[0339] <Other Applications>

[0340] The catalyst composition of the present invention can be used as a catalyst in various reactions. Specifically, for example, it can be used for the hydrogenation of unsaturated bonds in alkenes, acetylenes, aromatic rings, aldehydes, α, β unsaturated aldehydes, etc., the hydrogenation decomposition of hydrocarbons, hydrogen transfer reactions, etc. The transition metal supported in this case is not particularly limited, and Ni, Pd, Pt, Rh, Ru, etc. are commonly used.

[0341] In this invention, the raw material can be either ammonia diluted with a balance gas or ammonia alone, i.e., ammonia gas with a volume fraction of 0.1% to 100%. When producing hydrogen using the ammonia decomposition reaction, it is necessary to separate the generated hydrogen from the nitrogen; therefore, a higher ammonia volume fraction is preferred, preferably 5% or more, more preferably 20% or more, and even more preferably 70% or more. A higher NH3 conversion rate can be obtained by carrying out the decomposition reaction under conditions where the weight hourly space velocity (WHSV) is 500 ml g⁻¹ h⁻¹ or higher.

[0342] Regarding the gas generated using the ammonia decomposition method of the present invention, theoretically, hydrogen and nitrogen are obtained in a molar ratio of 3:1, and it can be used, for example, as a gas for bright annealing of stainless steel, nickel steel, nickel, nickel-copper, or nickel-chromium alloys. Furthermore, the hydrogen obtained in the present invention does not contain CO or CO2, which are harmful to fuel cells; therefore, the generated hydrogen and nitrogen can be separated and purified for use, for example, as hydrogen for fuel cells.

[0343] Preferred methods and specific examples of catalyst compositions used in other applications such as ammonia decomposition reactions can be found in the preferred methods and specific examples described in the first and second embodiments of the aforementioned catalyst compositions.

[0344] (Other embodiments regarding the use of catalyst additives)

[0345] As another embodiment of the use of the catalyst additive, the use of the catalyst additive represented by the following formula (1) for the following reaction is given, which is a reaction in which a mixture obtained by adding or mixing the catalyst additive to a chemical reaction catalyst or its precursor is carried out at a temperature below 700°C and in the presence of a reducing gas or an inactive gas in a catalytic activity promoting reaction, which promotes the electron-donating ability of the chemical reaction catalyst and thus promotes catalytic activity.

[0346] L m A n (1)

[0347] (In formula (1),)

[0348] L indicates that at least one element is selected from the group consisting of free transition elements and aluminum (Al).

[0349] A represents at least one element selected from the group consisting of silicon (Si), oxygen (O), nitrogen (N), and carbon (C).

[0350] (m represents a value greater than 1, and n represents a value greater than 0.)

[0351] The use of the catalyst additives in this embodiment relates to chemical reaction catalysts and catalyst additives that are preferably embodiments and preferred examples of the various chemical reaction catalysts and catalyst additives described in the aforementioned catalyst compositions. Their descriptions are incorporated herein by reference.

[0352] Example

[0353] The present invention will now be described in more detail based on embodiments.

[0354] The amount of NH3 generated can be quantified using gas chromatography, or the generated NH3 can be dissolved in an aqueous sulfuric acid solution and the solution can be quantified using ion chromatography to determine the ammonia generation rate, thereby evaluating the ammonia synthesis activity.

[0355] (Ion chromatography analysis)

[0356] The ammonia gas discharged from the reaction vessel was dissolved in a 5 mM sulfuric acid aqueous solution, and the captured ammonium ions (NH4+) were analyzed using an ion chromatograph. + The analysis will be performed under the following conditions.

[0357] [Measurement Conditions]

[0358] Equipment: Prominence manufactured by Shimadzu Corporation

[0359] Detector: Conductivity detector CDD-10Avp (manufactured by Shimadzu Corporation)

[0360] Column: IC-C4 column for ion chromatography (manufactured by Shimadzu Corporation)

[0361] Eluent: 3.0 mM oxalic acid + 2.0 mM 18-crown-6-ether aqueous solution

[0362] Flow rate: 1.0 mL / min

[0363] Column temperature: 40℃

[0364] (Example 1)

[0365] (Preparation of the catalyst composition (catalyst for ammonia synthesis))

[0366] [Synthesis of Ru / Ba-MgO powder with added TiSi]

[0367] (I) Preparation of a mixture of Ru / Ba-MgO precursor and TiSi as a chemical reaction catalyst

[0368] The MgO used was a product of Ube Material Industries, Ltd. (average particle size: 50nm, purity: 99.98%, model: 500A).

[0369] An aqueous solution was prepared from 0.0648 g of Ba(NO3)2, 0.1714 g of Ru(NO)(NO3)3 (equivalent to 5% by mass relative to Ba-MgO, based on the supported metallic Ru), and 1.3 g of distilled water. 1.0 g of MgO powder was added to the aqueous solution, and the mixture was kneaded in a mortar for approximately 15 minutes to obtain a brown paste. 0.364 g of TiSi (equivalent to 25% by mass relative to Ru / Ba-MgO) was added to the obtained paste, and the mixture was kneaded in a mortar. The resulting mixture was then dried at 140°C for approximately 2 hours to obtain a mixture of TiSi + MgO + Ba(NO3)2 + Ru(NO)(NO3)3.

[0370] (II) Under a nitrogen atmosphere at atmospheric pressure, the mixture obtained above was heated from room temperature to 400°C at a heating rate of 5°C / min, and then held at 450°C for 4 hours. It was then cooled to room temperature to obtain Ru / Ba-MgO powder with TiSi added, which was used as the catalyst composition (catalyst for ammonia synthesis) in this embodiment.

[0371] [Ammonia synthesis using Ru / Ba-MgO with added TiSi]

[0372] <Ammonia Synthesis Reaction>

[0373] The aforementioned Ru / Ba-MgO with added TiSi was used as a catalyst, and this catalyst was contacted with a mixture of nitrogen and hydrogen gas (N2 / H2 = 1 / 3 (v / v)) to carry out an ammonia synthesis reaction. 0.1 g of the aforementioned Ru / Ba-MgO with added TiSi was packed into a SUS-made reaction tube, and the reaction was carried out using a fixed-bed flow-through reactor assembled with this reaction tube. The moisture concentrations of the nitrogen and hydrogen in the feedstock were below the detection limit. The flow rates of the feedstock gases during the reaction were 15 mL / min for nitrogen and 45 mL / min for hydrogen (total 60 mL / min). Furthermore, the reaction pressure was 0.9 MPa, the reaction temperature was 400 °C, and the reaction time was 30 hours. It should be noted that a pretreatment reaction was performed under the same conditions as the ammonia synthesis reaction described above, at 450 °C for 20 hours. The catalytic activity was then evaluated under the established reaction conditions.

[0374] In addition, ammonia synthesis was also carried out at a reaction pressure of 0.9 MPa, a reaction temperature of 340 °C, and a reaction time of 30 hours.

[0375] <Ammonia formation rate>

[0376] The gas exiting the aforementioned fixed-bed flow-through reactor was bubbled in a 0.005M sulfuric acid aqueous solution, thereby dissolving the ammonia in the gas into the aqueous solution. The ammonium ions produced in the aqueous solution were quantified using the aforementioned method with an ion chromatograph. The rate of ammonia production from the ammonia synthesis reaction was determined over time using an ion chromatograph. The results showed that Ru / Ba-MgO with added TiSi exhibited higher catalytic activity than Ru / Ba-MgO as a catalyst without added TiSi (shown in...). Figure 4 (as shown in Table 1).

[0377] The ammonia generation rate of the Ru / Ba-MgO catalyst with TiSi added at 400℃ was 39.4 mmol / g·hr.

[0378] Show their results Figure 1 .

[0379] <Changes in the ammonia synthesis reaction over time>

[0380] The reaction time was varied, and otherwise, the ammonia synthesis rate at 400 °C and 0.9 MPa was measured in the same manner as above. The results are presented below. Figure 7 Even after continuous reaction for more than 300 hours, the ammonia production rate of the Ru / Ba-MgO catalyst with added TiSi hardly decreased, demonstrating stable catalytic activity.

[0381] (Examples 2-5)

[0382] [Synthesis of Ru / Ba-MgO powder with added TiSi]

[0383] TiSi was added in amounts of 0.0437 g (3 wt%), 0.146 g (10 wt%), 0.255 g (17.5 wt%), and 0.728 g (50 wt%), respectively. Otherwise, the Ru / Ba-MgO powders with TiSi added in Examples 2 to 5 were obtained by the same method as in Example 1.

[0384] [Ammonia synthesis using Ru / Ba-MgO with added TiSi]

[0385] <Ammonia Synthesis Reaction>

[0386] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 340°C and 0.9 MPa, and at 400°C and 0.9 MPa, were determined. The results are presented below. Figure 1 .

[0387] (Example 6)

[0388] The pretreatment conditions were nitrogen atmosphere and 600°C. Otherwise, the ammonia synthesis activity of Ru / Ba-MgO with added TiSi was evaluated under the same conditions as in Example 1. Specifically, the ammonia synthesis rate at 400°C and 0.9 MPa was measured. The results are shown below. Figure 2 It should be noted that, in Figure 2 The text describes the ammonia synthesis activity in a test zone at 450°C under the pretreatment conditions of a nitrogen and hydrogen mixture (N2 / H2 = 1 / 3 (v / v)) (i.e., the ammonia synthesis activity of Ru / Ba-MgO with TiSi added under the same conditions as in Example 1), and the ammonia synthesis activity in a test zone without TiSi added (i.e., the ammonia synthesis activity of Ru / Ba-MgO without TiSi added under the same conditions as in Comparative Example 1).

[0389] (Example 7)

[0390] The pretreatment temperature was 600°C. Otherwise, the ammonia synthesis activity of Ru / Ba-MgO with TiSi was evaluated under the same conditions as in Example 1.

[0391] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown below. Figure 4 .

[0392] (Example 8)

[0393] [Fe loading onto Ba-MgO]

[0394] Instead of Ru(NO)(NO3)3, 1.8 g of Fe(NO3)3·9(H2O) was used (equivalent to 20% by mass relative to Ba-MgO based on the supported metallic Fe). Otherwise, the Fe / Ba-MgO powder with TiSi added in this embodiment was obtained by the same method as in Example 1.

[0395] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown below. Figure 4 .

[0396] (Example 9)

[0397] The pretreatment temperature was 600°C. Otherwise, the ammonia synthesis activity of Fe / Ba-MgO with added TiSi was evaluated under the same conditions as in Example 8. The results are shown below. Figure 4 .

[0398] (Example 10)

[0399] [Co-supported in Ba-MgO]

[0400] Instead of Ru(NO)(NO3)3, 0.118 g of Co2(CO)8 (equivalent to 8% by mass relative to Ba-MgO based on the supported metallic Co) was used. Otherwise, the TiSi-added Co / Ba-Mg O powder of this embodiment was obtained by the same method as in Example 1.

[0401] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown below. Figure 4 .

[0402] (Example 11)

[0403] The pretreatment temperature was 600°C. Otherwise, the ammonia synthesis activity of Co / Ba-MgO with added TiSi was evaluated under the same conditions as in Example 10. The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown below. Figure 4 .

[0404] Catalyst additives other than TiSi

[0405] (Example 12)

[0406] Ti was used instead of TiSi (25% by mass relative to Ru / Ba-MgO), and the Ti-added Ru / Ba-MgO powder of this embodiment was otherwise obtained by the same method as in Example 1.

[0407] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The rate of ammonia synthesis at 400°C and 0.9 MPa was determined. The results are presented below. Figure 5 In addition, the ammonia synthesis rate at 340℃ and 0.9 MPa was determined. The results are presented below. Figure 6 .

[0408] (Example 13)

[0409] TiO was used instead of TiSi (25% by mass relative to Ru / Ba-MgO), and the Ru / Ba-MgO powder with TiO added in this embodiment was otherwise obtained by the same method as in Example 1.

[0410] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The rate of ammonia synthesis at 400°C and 0.9 MPa was determined. The results are presented below. Figure 5 In addition, the ammonia synthesis rate at 340℃ and 0.9 MPa was determined. The results are presented below. Figure 6 .

[0411] (Example 14)

[0412] 0.364 g of TiN was used instead of TiSi (an addition of 25% by mass relative to Ru / Ba-MgO). Otherwise, the Ru / Ba-MgO powder with TiN added in this embodiment was obtained by the same method as in Example 1.

[0413] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The rate of ammonia synthesis at 400°C and 0.9 MPa was determined. The results are presented below. Figure 5 In addition, the ammonia synthesis rate at 340℃ and 0.9 MPa was determined. The results are presented below. Figure 6 .

[0414] (Example 15)

[0415] TiC 0.364g was used instead of TiSi (25% by mass relative to Ru / Ba-MgO), otherwise, the Ru / Ba-MgO powder with TiC added in this embodiment was obtained by the same method as in Example 1.

[0416] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The rate of ammonia synthesis at 400°C and 0.9 MPa was determined. The results are presented below. Figure 5 In addition, the ammonia synthesis rate at 340℃ and 0.9 MPa was determined. The results are presented below. Figure 6 .

[0417] (Example 16)

[0418] Instead of TiSi, 0.364 g of Fe was used (an addition of 25% by mass relative to Ru / Ba-MgO). Otherwise, the Fe-added Ru / Ba-MgO powder of this embodiment was obtained by the same method as in Example 1.

[0419] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The rate of ammonia synthesis at 400°C and 0.9 MPa was determined. The results are presented below. Figure 5 In addition, the ammonia synthesis rate at 340℃ and 0.9 MPa was determined. The results are presented below. Figure 6 .

[0420] (Example 17)

[0421] Instead of TiSi, 0.364 g of Ni was used (an addition of 25% by mass relative to Ru / Ba-MgO). Otherwise, the Ru / Ba-MgO powder with Ni added in this embodiment was obtained by the same method as in Example 1.

[0422] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The rate of ammonia synthesis at 400°C and 0.9 MPa was determined. The results are presented below. Figure 5 In addition, the ammonia synthesis rate at 340℃ and 0.9 MPa was determined. The results are presented below. Figure 6 .

[0423] (Example 18)

[0424] Al 0.364g was used instead of TiSi (25% by mass relative to Ru / Ba-MgO), otherwise the Al-added Ru / Ba-MgO powder of this embodiment was obtained by the same method as in Example 1.

[0425] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The rate of ammonia synthesis at 400°C and 0.9 MPa was determined. The results are presented below. Figure 5 In addition, the ammonia synthesis rate at 340℃ and 0.9 MPa was determined. The results are presented below. Figure 6 .

[0426] (Example 19)

[0427] Instead of TiSi, 0.364 g of Si was used (25% by mass relative to Ru / Ba-MgO). Otherwise, the Ru / Ba-MgO powder with added Si in this embodiment was obtained by the same method as in Example 1.

[0428] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The rate of ammonia synthesis at 400°C and 0.9 MPa was determined. The results are presented below. Figure 5 .

[0429] (Comparative Example 1)

[0430] [Synthesis of Ru / Ba-MgO powder]

[0431] Without adding TiSi, Ru / Ba-MgO powder was obtained by the same method as in Example 1.

[0432] <Ammonia Synthesis Reaction>

[0433] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rates at 340°C and 400°C, and 0.9 MPa were determined. The results are presented below. Figures 1-3 Table 1.

[0434] (Comparative Example 2)

[0435] The pretreatment conditions were 600°C. Otherwise, the ammonia synthesis rate was measured at 400°C and 0.9 MPa under the same conditions as Comparative Example 1 to evaluate the ammonia synthesis activity of Ru / Ba-MgO. The results are shown below. Figure 3 .

[0436] (Comparative Example 3)

[0437] [Synthesis of Ru / TiSi powder]

[0438] An aqueous solution was prepared from 0.1714 g of Ru(NO)(NO3)3 (equivalent to 5% by mass relative to TiSi, based on the supported metallic Ru) and 1.3 g of distilled water. 1.0 g of TiSi powder was added to the aqueous solution, and the mixture was kneaded in a mortar for approximately 15 minutes. The resulting mixture was then dried at 140°C for approximately 2 hours to obtain a mixture of TiSi and Ru(NO)(NO3)3.

[0439] (2) Under a nitrogen atmosphere at atmospheric pressure, the mixture obtained above was heated from room temperature to 400°C at a heating rate of 5°C / min, and then held at 450°C for 4 hours. Then, it was cooled to room temperature to obtain the Ru / TiSi powder of this comparative example as the catalyst composition (catalyst for ammonia synthesis) of this embodiment.

[0440] <Ammonia Synthesis Reaction>

[0441] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are presented in... Figure 3 .

[0442] (Comparative Example 4)

[0443] [Fe loading onto Ba-MgO]

[0444] Instead of Ru(NO)(NO3)3, 1.8 g of Fe(NO3)3·9(H2O) was used (equivalent to 20% by mass relative to Ba-MgO based on the supported metallic Fe). Otherwise, the Fe / Ba-MgO powder of this comparative example was obtained by the same method as that of Comparative Example 1.

[0445] <Ammonia Synthesis Reaction>

[0446] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The rate of ammonia synthesis at 400°C and 0.9 MPa was determined. The results are presented below. Figure 4 .

[0447] (Comparative Example 5)

[0448] The pretreatment conditions were 600°C. Otherwise, the ammonia synthesis activity of Fe / Ba-MgO was evaluated under the same conditions as in Comparative Example 4. The results are shown below. Figure 4 .

[0449] (Comparative Example 6)

[0450] [Co-supported in Ba-MgO]

[0451] Instead of Ru(NO)(NO3)3, 0.118 g of Co2(CO)8 (equivalent to 8% by mass relative to Ba-MgO based on the supported metallic Co) was used. Otherwise, the Co / Ba-MgO powder of this comparative example was obtained by the same method as that of Comparative Example 1.

[0452] <Ammonia Synthesis Reaction>

[0453] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The rate of ammonia synthesis at 400°C and 0.9 MPa was determined. The results are presented below. Figure 4 .

[0454] (Comparative Example 7)

[0455] The pretreatment conditions were 600°C. Otherwise, the ammonia synthesis activity of Co / Ba-MgO was evaluated under the same conditions as in Comparative Example 6. The results are shown below. Figure 4 .

[0456] (Example 20)

[0457] (Preparation of the catalyst composition (catalyst for ammonia synthesis))

[0458] [Synthesis of Ru / Sr-MgO powder with added TiSi]

[0459] (I) Preparation of a mixture of Ru / Sr-MgO precursor and TiSi as a chemical reaction catalyst

[0460] An aqueous solution was prepared from 0.0525 g of Sr(NO3)2, 0.1714 g of Ru(NO)(NO3)3 (equivalent to 5% by mass relative to Ba-MgO, based on the supported metallic Ru), and 1.3 g of distilled water. 1.0 g of MgO powder was added to the aqueous solution, and the mixture was kneaded in a mortar for approximately 15 minutes to obtain a paste. 0.364 g of TiSi (equivalent to 25% by mass relative to Ru / Sr / MgO) was added to the obtained paste, and the mixture was kneaded in a mortar. The resulting mixture was then dried at 140 °C for approximately 2 hours, thus obtaining a mixture of TiSi + MgO + Sr(NO3)2 + Ru(NO)(NO3)3.

[0461] (II) Under a nitrogen atmosphere at atmospheric pressure, the mixture obtained above was heated from room temperature to 400°C at a heating rate of 5°C / min, and then held at 450°C for 4 hours. It was then cooled to room temperature to obtain Ru / Sr-MgO powder with TiSi added, which was used as the catalyst composition (catalyst for ammonia synthesis) in this embodiment.

[0462] <Ammonia Synthesis Reaction>

[0463] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown in Table 1.

[0464] (Example 21)

[0465] (Preparation of the catalyst composition (catalyst for ammonia synthesis))

[0466] [Synthesis of Ru / BaAl2O4 powder with added TiSi]

[0467] (I) Preparation of a mixture of Ru / BaAl2O4 precursor and TiSi as a chemical reaction catalyst

[0468] 0.148 g of barium carbonate (pure chemical, 99.9%) and 0.117 g of aluminum hydroxide (high-purity chemical, 99.99%) were mixed in a Ba:Al molar ratio of 1:2. The resulting mixture was placed in an alumina crucible and heated to 1000 °C for 3 hours, then maintained at that temperature for 10 hours to obtain BaAl₂O₄ oxide.

[0469] The obtained powdered BaAl2O4 0.50g and Ru3(CO) were mixed. 120.056 g (equivalent to 5% by mass of the supported Ru relative to BaAl₂O₄) of Ru₃(CO) was packed into a silica glass tube and heated at 70°C for 1 hour in a vacuum. Then, it was heated further at 120°C for 1 hour, thereby converting Ru₃(CO) into its constituent elements. 12 It adheres to the surface of powdered BaAl2O4.

[0470] The Ru3(CO) coating obtained as described above 12 Powdered BaAl2O4 was heated at 250℃ for 2 hours to react with Ru3(CO). 12 Thermal decomposition yields a support material with Ru fixed on BaAl2O4 (hereinafter referred to as Ru / BaAl2O4).

[0471] The obtained powdered Ru / BaAl2O4 1.0 g, TiSi 0.364 g, and dodecane 1.3 g were mixed in a mortar. The resulting mixture was dried at 140 °C for about 2 hours. Under a nitrogen atmosphere at atmospheric pressure, the temperature was increased from room temperature to 400 °C at a rate of 5 °C / min, and then held at 450 °C for 4 hours. The mixture was then cooled to room temperature to obtain a mixture of TiSi + Ru / BaAl2O4.

[0472] <Ammonia Synthesis Reaction>

[0473] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown in Table 1.

[0474] [Table 1]

[0475]

[0476] (Example 22)

[0477] (Preparation of the catalyst composition (catalyst for ammonia synthesis))

[0478] [Synthesis of Ru / CeO2 powder with added TiSi]

[0479] (I) Preparation of a mixture of Ru / CeO2 precursor and TiSi as a chemical reaction catalyst

[0480] An aqueous solution was prepared from 0.1714 g of Ru(NO)(NO3)3 (equivalent to 5% by mass relative to CeO2, based on the supported metallic Ru) and 1.3 g of distilled water. 1.0 g of CeO2 powder was added to the aqueous solution, and the mixture was kneaded in a mortar for approximately 15 minutes to obtain a paste. 0.364 g of TiSi (equivalent to 25% by mass relative to Ru / CeO2) was added to the obtained paste, and the mixture was kneaded in a mortar. The resulting mixture was then dried at 140°C for approximately 2 hours, thus obtaining a mixture of TiSi + CeO2 + Ru(NO)(NO3)3.

[0481] (II) Under a nitrogen atmosphere at atmospheric pressure, the mixture obtained above was heated from room temperature to 400°C at a heating rate of 5°C / min, and then held at 450°C for 4 hours. It was then cooled to room temperature to obtain Ru / CeO2 powder with TiSi added, which was used as the catalyst composition (catalyst for ammonia synthesis) in this embodiment.

[0482] <Ammonia Synthesis Reaction>

[0483] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown in Table 1.

[0484] (Example 23)

[0485] (Preparation of the catalyst composition (catalyst for ammonia synthesis))

[0486] Synthesis of Ru / Ba-CeO2 powder with added TiSi

[0487] (I) Preparation of a mixture of Ru / Ba-CeO2 precursor and TiSi as a chemical reaction catalyst

[0488] An aqueous solution was prepared from 0.0648 g of Ba(NO3)2, 0.1714 g of Ru(NO)(NO3)3 (equivalent to 5% by mass relative to Ba-CeO2 based on the supported metallic Ru), and 1.3 g of distilled water. 1.0 g of CeO2 powder was added to the aqueous solution, and the mixture was kneaded in a mortar for approximately 15 minutes to obtain a paste. 0.364 g of TiSi (equivalent to 25% by mass relative to Ru / Ba-CeO2) was added to the obtained paste, and the mixture was kneaded in a mortar. The resulting mixture was then dried at 140°C for approximately 2 hours, thus obtaining a mixture of TiSi + CeO2 + Ba(NO3)2 + Ru(NO)(NO3)3.

[0489] (II) Under a nitrogen atmosphere at atmospheric pressure, the mixture obtained above was heated from room temperature to 400°C at a heating rate of 5°C / min, and then held at 450°C for 4 hours. It was then cooled to room temperature to obtain Ru / Ba-CeO2 powder with TiSi added, which was used as the catalyst composition (catalyst for ammonia synthesis) in this embodiment.

[0490] <Ammonia Synthesis Reaction>

[0491] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown in Table 1.

[0492] (Comparative Example 8)

[0493] [Synthesis of Ru / Sr-MgO powder]

[0494] Without adding TiSi, Ru / Sr-MgO powder was obtained by the same method as in Example 20.

[0495] <Ammonia Synthesis Reaction>

[0496] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown in Table 1.

[0497] (Comparative Example 9)

[0498] [Synthesis of Ru / BaAl2O4 powder]

[0499] Without adding TiSi, Ru / BaAl2O4 powder was obtained by the same method as in Example 21.

[0500] <Ammonia Synthesis Reaction>

[0501] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown in Table 1.

[0502] (Comparative Example 10)

[0503] [Synthesis of Ru / CeO2 powder]

[0504] Without adding TiSi, Ru / CeO2 powder was obtained by the same method as in Example 22.

[0505] <Ammonia Synthesis Reaction>

[0506] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown in Table 1.

[0507] (Comparative Example 11)

[0508] [Synthesis of Ru / Ba-CeO2 powder]

[0509] Without adding TiSi, Ru / Ba-CeO2 powder was obtained by the same method as in Example 23.

[0510] <Ammonia Synthesis Reaction>

[0511] The ammonia synthesis reaction was carried out under the same conditions as in Example 1. The ammonia synthesis rate at 400°C and 0.9 MPa was determined. The results are shown in Table 1.

[0512] (discuss)

[0513] The results of the various embodiments and comparative examples shown in the figures and tables are described below. This invention is not limited to the configurations of the embodiments.

[0514]

[0515] It was confirmed that the ammonia synthesis activity was enhanced by adding TiSi, a catalyst additive used in other chemical reaction catalysts, in addition to the Ru / Ba-MgO catalyst. It is believed that in chemical reaction catalysts using rare earth oxides such as Ru / CeO2 as supports, the addition of TiSi allows for oxygen abstraction from the aforementioned oxides without high-temperature hydrogen reduction, achieving the same effect. Furthermore, the same effect is observed even with Ba-containing metal oxides such as BaAl2O4, suggesting that the effect of TiSi addition can be seen for other Ba-containing composite oxides. Moreover, even with Ru / Sr-MgO catalysts where Sr is added instead of Ba, an increase in ammonia synthesis activity due to TiSi addition was confirmed. In the case of the Ru / Ba-MgO catalyst, which exhibits the highest activity, the main reason for the high effect of TiSi addition is believed to be the formation of oxygen vacancies in BaO rather than MgO, resulting in high catalytic activity due to the electron supply from electrons formed at its F centers. Furthermore, in the case of SrO catalyst, it is considered to be less prone to forming oxygen vacancies than BaO. By adding TiSi, oxygen vacancies are formed in SrO, exhibiting electron-donating properties.

[0516] < Figure 1 >

[0517] according to Figure 1 The relationship between the amount of catalyst additive added and the catalyst effect is shown for the catalyst compositions (ammonia synthesis catalysts) of this embodiment in Examples 1 to 5.

[0518] Compared with the ammonia generation rate of the Ru / Ba-MgO catalyst before the addition of TiSi (21.8 mmol / g·hr), the more TiSi was added, the higher the ammonia generation rate became, reaching the maximum when 25 wt% TiSi was added.

[0519] < Figure 2 >

[0520] Even with pretreatment at 600°C under a N2 atmosphere only, the ammonia synthesis activity of the Ru / Ba-MgO catalyst with TiSi was equivalent to that of the Ru / Ba-MgO catalyst with TiSi pretreatment at 450°C under a N2+H2 atmosphere. This demonstrates that even without hydrogen during pretreatment, the catalyst can be activated via reduction in the presence of a reducing agent such as TiSi.

[0521] < Figure 3 >

[0522] Under the same conditions as in Example 1, the ammonia synthesis activity of the Ru / Ba-MgO catalyst with added TiSi was compared and evaluated with the ammonia synthesis activity of the catalyst formed by pretreating the Ru / Ba-MgO catalyst without added TiSi at 600°C.

[0523] Generally speaking, Ru-based catalysts often exhibit significantly enhanced catalytic activity when subjected to high-temperature reduction in a hydrogen-containing atmosphere. For example... Figure 3 As shown, for the Ru / Ba-MgO catalyst, the ammonia formation rate was 21.8 mmol / g·hr after pretreatment at 450 °C, and increased to 40.3 mmol / g·hr after pretreatment at 600 °C. On the other hand, the ammonia synthesis activity of the TiSi-added Ru / Ba-MgO catalyst pretreated at 450 °C was equivalent to that of the Ru / Ba-MgO catalyst without TiSi or other catalyst additives pretreated at 600 °C. In the case of the Ru / TiSi catalyst, there was almost no ammonia synthesis activity, indicating that TiSi itself does not have a catalytic effect, but rather promotes the catalytic activity of the catalyst composition containing the Ru / Ba-MgO catalyst at a lower temperature. It is believed that the formation of oxygen vacancies in BaO using TiSi significantly enhances the activity of the Ru catalyst due to the electron supply from the F centers formed immediately below the lower end of the BaO conduction band.

[0524] < Figure 4 >

[0525] With a pretreatment temperature of 450°C, the addition of TiSi increased the ammonia synthesis activity of the Ru / Ba-MgO catalyst by approximately 1.8 times, while with a pretreatment temperature of 600°C, the addition of TiSi increased the ammonia synthesis activity of the Ru / Ba-MgO catalyst by approximately 1.26 times. As stated above, this indicates that although the increase in ammonia synthesis activity was relatively small, the experimental system with TiSi added during the high-temperature pretreatment showed a greater effect in promoting catalytic activity.

[0526] Furthermore, for catalyst compositions that use metal-supported catalysts with Fe or Co instead of Ru as chemical reaction catalysts (metal-supported catalysts) and add TiSi as a catalyst additive to the metal-supported catalyst, the ammonia synthesis activity is improved compared to the catalyst without catalyst additives, similar to Ru / Ba-MgO with added TiSi.

[0527] Furthermore, under a pretreatment at 450°C, the ammonia synthesis activity of the Fe / Ba-MgO catalyst remained almost unchanged upon the addition of TiSi, while under a pretreatment at 600°C, the ammonia synthesis activity of the Fe / Ba-MgO catalyst increased by approximately 1.5 times upon the addition of TiSi. This indicates that even with the addition of TiSi, relatively strong pretreatment conditions are required when Fe is supported.

[0528] On the other hand, with a pretreatment temperature of 450°C, the ammonia synthesis activity of the Co / Ba-MgO catalyst was increased by approximately 1.8 times by adding TiSi. With a pretreatment temperature of 600°C, the ammonia synthesis activity of the Co / Ba-MgO catalyst was increased by approximately 1.5 times by adding TiSi.

[0529] < Figure 5 and Figure 6 >

[0530] By pretreatment of Ru / Ba-MgO catalysts with various substances added as catalyst additives instead of TiSi to enhance the catalytic activity of the catalyst composition, the ammonia synthesis activity was significantly improved in most tested substances compared to the original Ru / Ba-MgO catalyst (without catalyst additives). The effect of this catalyst additive was particularly significant in experimental systems using Ti-based compounds. Specifically, the effect of adding Ti to the ammonia synthesis activity was higher than that of adding TiSi. On the other hand, the effect of adding Si was almost imperceptible (i.e., no improvement in ammonia synthesis activity). It should be noted that although the main reason for the improved ammonia activity caused by the catalyst additive of the present invention is not yet fully understood, it is believed that the tested substances added to the catalyst composition are all easily oxidized and extract oxygen from BaO present in the Ru / Ba-MgO catalyst. Among alkaline earth metal oxides, BaO has low oxygen defect formation energy, and the F center is formed just below the lower end of the conduction band, thus becoming an electron donor. It is believed that it acts as an electron promoter, which, as a result, greatly enhances the activity of Ru catalysts.

[0531] <Effects of Catalyst Additives>

[0532] While the reaction mechanism related to the effects shown in the above embodiments has not yet been elucidated, it is believed that oxides such as BaO, where F centers are formed near the lower end of the conduction band when oxygen vacancies are formed, and which can form surfaces with low work functions, exhibit high electron-donating properties. It is considered important to add substances with high oxygen-extraction capabilities, such as TiSi, as catalyst additives to the chemical reaction catalyst when such oxygen vacancies are formed.

[0533] The aforementioned catalyst additives are used as co-catalysts or co-catalyst-like substances for the aforementioned chemical reaction catalysts.

[0534] The term "catalyst-like substance" as used here refers to the following substances: substances that, when alone, do not possess the catalytic activity of the aforementioned chemical reaction catalysts as a target or object of the catalytic reaction, but together with the target or object of the reaction catalyst, have the effect of assisting the catalytic chemical reaction accelerated by the reaction catalyst (enhancing the catalytic activity exhibited by the reaction catalyst alone, or compensating for the shortcomings of the reaction catalyst).

[0535] The term "catalyst" as used here refers to a substance that does not act as a catalyst on its own, but together with the target catalyst, assists in accelerating the catalytic chemical reaction (enhancing the catalytic effect exhibited by the catalyst alone, or compensating for the shortcomings of the catalyst).

[0536] For example, the reaction mechanism is considered to be the following mechanism.

[0537] As a co-catalyst, the titanium silicide (TiSix) and other catalyst additives of Example 1 abstract oxygen ions from the crystal structure of the chemical reaction catalyst (e.g., oxides such as BaO / CeO2) and replace them with electrons. The electrons themselves become anions, forming an ionic crystal (i.e., an electron compound). With respect to this ionic crystal, the ease of electron extraction is no different compared to alkali metals, but it is chemically and thermally stable even under atmospheric conditions. Moreover, the aforementioned electrons play a role, for example, in the cleavage of the nitrogen-nitrogen triple bond, thereby promoting the ammonia synthesis reaction.

[0538] On the other hand, it is known that in the absence of existing catalysts containing co-catalysts, the catalytic activity of the reaction is increased when a "catalytically active metal component" such as Ru is added to the reaction catalyst and then subjected to hydrogen reduction at high temperature. Therefore, problems exist such as reduced catalyst stability and high load on the reaction apparatus caused by high-temperature hydrogen treatment. By using the catalyst additive of the present invention as a co-catalyst, it is expected that the reduction in catalyst stability can be suppressed and the load on the reaction apparatus caused by high-temperature hydrogen treatment can be reduced.

Claims

1. A catalyst composition, characterized in that, Include: The catalyst additives represented by the following formula (1), and A chemical reaction catalyst containing a catalytic substance represented by the following formula (2-1), L m A n (1) In equation (1), L represents titanium (Ti). A indicates that at least one of the following is selected from the group consisting of silicon (Si), nitrogen (N), and carbon (C). m represents a value greater than 1, and n represents a value greater than 0; M p O q (2-1) In equation (2-1), M represents one or more elements selected from the group consisting of barium (Ba), cerium (Ce), magnesium (Mg), calcium (Ca), strontium (Sr), lanthanum (La), silicon (Si), and aluminum (Al), wherein M does not simultaneously include aluminum (Al) and calcium (Ca). p represents a value greater than 1, and q represents a value greater than 1.

2. The catalyst composition of claim 1, wherein, The chemical reaction catalyst and the catalyst composition have hydrogenation reaction activity. The hydrogenation activity of the catalyst composition is higher than that of the chemical reaction catalyst.

3. The catalyst composition according to claim 2, wherein, The hydrogenation reaction activity of the chemical reaction catalyst and the catalyst composition is ammonia synthesis activity.

4. The catalyst composition according to claim 2 or 3, wherein, The catalyst additive does not have hydrogenation reaction activity.

5. The catalyst composition according to any one of claims 1 to 3, wherein, The catalyst additive is selected from at least one of the groups consisting of Ti, TiSi, and TiC.

6. The catalyst composition according to any one of claims 1 to 3, wherein, The catalyst is selected from one of the following groups: Ba-MgO, Sr-MgO, BaAl2O4, CeO2, and Ba-CeO2.

7. The catalyst composition according to any one of claims 1 to 3, wherein, The chemical reaction catalyst further comprises at least one catalytically active metal selected from the group consisting of ruthenium (Ru), cobalt (Co), iron (Fe), nickel (Ni), molybdenum (Mo), rhodium (Rh), rhenium (Re), chromium (Cr), and manganese (Mn). The chemical reaction catalyst is a metal-supported material obtained by supporting the catalytically active metal on a support. The support is the catalyst material represented by formula (2-1).

8. The catalyst composition of claim 7, wherein, The carrier may contain silicon (Si), oxygen (O) and aluminum (Al) simultaneously.

9. The catalyst composition according to claim 7, characterized in that, The support is an alkaline metal oxide.

10. The catalyst composition according to claim 9, characterized in that, The support is a crystalline alkaline metal oxide.

11. The catalyst composition according to any one of claims 1 to 3, wherein, The catalyst additive is at least one selected from the group consisting of Ti, TiSi, TiN, and TiC. The catalyst is selected from one of the following groups: Ba-MgO, Sr-MgO, BaAl2O4, CeO2, and Ba-CeO2. The chemical reaction catalyst also contains a catalytically active metal. The chemical reaction catalyst is a metal-supported material obtained by supporting the catalytically active metal on a support. The support is the catalyst material. The catalytically active metal is selected from one of the groups consisting of Ru, Co, and Fe.

12. A method for promoting catalytic activity, which enhances the electron-donating ability of a chemical reaction catalyst to promote catalytic activity, the method comprising the step of adding or mixing a catalyst additive into the chemical reaction catalyst or its precursor, characterized in that... The process includes a step of reacting a mixture obtained by adding or mixing the catalyst additive into a chemical reaction catalyst or its precursor at a temperature below 700°C in the presence of a reducing gas or nitrogen. The catalyst additive is a catalyst additive represented by the following formula (1). The chemical reaction catalyst is a chemical reaction catalyst containing a catalyst substance represented by the following formula (2-1). L m A n (1) In equation (1), L represents titanium (Ti). A indicates that at least one of the following is selected from the group consisting of silicon (Si), nitrogen (N), and carbon (C). m represents a value greater than 1, and n represents a value greater than 0; M p O q (2-1) In equation (2-1), M indicates that the composition is selected from one or more elements in the group consisting of barium (Ba), cerium (Ce), magnesium (Mg), calcium (Ca), strontium (Sr), lanthanum (La), silicon (Si), and aluminum (Al). p represents a value greater than 1, and q represents a value greater than 1.

13. The method for promoting catalytic activity as described in claim 12, wherein, The temperature conditions are below 600℃.

14. The method for promoting catalytic activity as described in claim 12 or 13, wherein, The chemical reaction catalyst also contains a catalytically active metal. The chemical reaction catalyst is a metal-supported material obtained by supporting the catalytically active metal on a support. The support is the catalyst material represented by formula (2-1).

15. The method for promoting catalytic activity as described in claim 12 or 13, wherein, The catalytic activity is hydrogenation reaction activity.

16. The method for promoting catalytic activity as described in claim 15, wherein, The hydrogenation reaction activity is ammonia synthesis activity.

17. The method for promoting catalytic activity as described in claim 12 or 13, wherein, The catalyst additive does not have hydrogenation reaction activity.

18. A method for manufacturing a catalyst composition, the method comprising the following steps: The first step involves mixing the catalyst additive with the chemical reaction catalyst or its precursor; and The second step involves reacting the first mixture obtained in the first step at a temperature below 700°C in the presence of a reducing gas or nitrogen. The catalyst additive is a catalyst additive represented by the following formula (1). The chemical reaction catalyst is a chemical reaction catalyst containing a catalyst substance represented by the following formula (2-1). L m A n (1) In equation (1), L represents titanium (Ti). A indicates that at least one of the following is selected from the group consisting of silicon (Si), nitrogen (N), and carbon (C). m represents a value greater than 1, and n represents a value greater than 0; M p O q (2-1) In equation (2-1), M indicates that the composition is selected from one or more elements in the group consisting of barium (Ba), cerium (Ce), magnesium (Mg), calcium (Ca), strontium (Sr), lanthanum (La), silicon (Si), and aluminum (Al). p represents a value greater than 1, and q represents a value greater than 1.

19. The method for manufacturing the catalyst composition according to claim 18, wherein, The temperature conditions are below 600℃.

20. A catalyst composition obtained by the method of manufacturing the catalyst composition according to claim 18.

21. A method for producing hydrides, characterized in that, The process includes reacting the feedstock compound to be hydrogenated with hydrogen in the presence of the catalyst composition according to any one of claims 1 to 3 and 20.

22. A method for producing ammonia, characterized in that, The process includes reacting nitrogen with hydrogen in the presence of the catalyst composition according to any one of claims 1 to 3 and 20.

Citation Information

Patent Citations

  • Ammonia synthesis catalyst and its production method

    JP2006231229A

  • Catalyst for ammonia synthesis and method for ammonia synthesis using the same

    JP2019126776A

  • Encoding device and method, program and storage medium

    JP2021182700A

  • Ammonia synthesis catalyst and ammonia synthesis method

    WO2012077658A1

  • Composite body, method for producing composite body, ammonia synthesis catalyst, and ammonia synthesis method

    WO2016088896A1